Pembuatan Standard Operating Procedure (SOP) Layanan Perpustakaan PT Semen Padang - T, Feggy Fristika Windu; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper discuss about the process of making Standard Operating Procedure (SOP) library serves in PT Semen. The aims of this study are to describe (1) the preparation of making Standard Operating Procedure (SOP) library serves in PT Semen; (2) making Standard Operating Procedure (SOP) library serves in PT Semen. The method used is the desscriptive method. The data collected through direct observation and asking some questions to the librarian in the library of PT Semen Padang. Based on the making Standard Operating Procedure (SOP), it can be concluded that making SOP as follows: (1) the preparation of making Standard Operating Procedure (SOP) library serves in PT Semen Padang; first, knowing the requirements, second, evaluating and assessing the requirements, third, choosing the requirements, fourth, choosing the alternative action; (2) making Standard Operating Procedure (SOP) library serves in PT Semen Padang; first, collected the informations, by discussing and interviewing with the head of department; second, making draft, experiments the instrument and asking the approval from the leader, experiments the instrument that exists with the draft of the SOP who have had discussion process; third, making and including the supporting document of SOP, including the supporting documents SOP are UU No. 43 tahun 2007 about library; fourth, includes the officer in making SOP and the persong who legalized it; fifth, includes the date of making, revision, and implementation of that.Keywords: Standard Operating Procedure (SOP), library of PT Semen Padang